Efforts to Increase Student Activity and Learning Outcomes with Flat Building Materials Using the Problem-Based Learning (PBL) Learning Model - Krisnamurti, Cyrenia Novella (Edumaspul: Jurnal Pendidikan, 2024)
This research aims to increase students’ activeness and learning outcomes regarding flat shapes by using the problem-based learning model in class III of SD N Ploso. This research is classroom action research. The data analysis technique uses qualitative and quantitative descriptive analysis. The subjects of this research were 4 students in class III of SD N Ploso. The research results show an increase in student activity and learning outcomes in each cycle. During the pre-cycle the average student learning activity was 25%, then in cycle I the average increased to 50% and in cycle II the average increased by 75%. Furthermore, the average value of student learning outcomes also increased in each cycle starting from the pre-cycle of 62.5. Furthermore, in cycle I it increased by 70, and in cycle II it increased again to 82.5. Based on the results of the research, it can be concluded that the use of the problem-based learning model can increase the activity and learning outcomes of class III students at SD N Ploso in the shape material.